Geographic Information System as an aid instrument for public policies and management of sports facilities and programs - Bruna Lindman Bueno; Leandro Carlos Mazzei; Alcides José Scaglia; Thomaz Chagas de Almeida (Universidade Estadual Paulista (UNESP), 2020)
Abstract Aims: This paper sought to evaluate the infrastructure of public swimming pools in a countryside municipality of the state of São Paulo and to present the Geographic Information System (GIS) as a tool capable of assisting in the management of sports facilities and programs. Methods: This is a descriptive study since it intends to expose the characteristics of a certain context. First, documentary research was performed to map the facilities and their respective projects. After that, a field survey was conducted seeking to evaluate the infrastructure of public pools and their surroundings through observation. Lastly, using georeferencing software, the population, and socioeconomic data around these pools were obtained and analyzed. Results: It was identified ten public swimming pools, and in seven the offer of swimming projects was foreseen. The infrastructure of the pools is mainly unsatisfactory, making necessary the improvement of the installation itself and in its surroundings. According to the results of the GIS, each pool has its specific public target concerning the characteristics of the profile of the residents surrounding these facilities. Conclusion: Information regarding the public profile around sports facilities generated from a tool such as GIS showed it is possible to determine which sports projects should be prioritized in each facility, leading to improvement in the management of sports-related public policies.